Virtual reality in problem‐based learning contexts: Effects on the problem‐solving performance, vocabulary acquisition and motivation of English language learners. (8th February 2021) - Chen, Ching‐Huei; Hung, Hsiu‐Ting; Yeh, Hui‐Chin
Abstract: Learning a foreign language requires interaction with language input while involved in a task. Given that problem‐based learning (PBL) offers hands‐on application in realistic contexts, and that virtual reality (VR) enables learners to interact with multiple modalities of information, this study examines how the integration of VR technology into PBL contexts affects students' motivation for, problem‐solving during, and vocabulary acquisition in learning English as a foreign language (EFL). A total of 84 engineering majors who enrolled in a course of English for specific purposes were randomly assigned to either an experimental group or a control group. Students in the experimental group participated in a VR‐assisted PBL context, in which they were to view a PBL scenario using VR technology and then to create VR videos about solving the given problems. Those in the control group participated in a PBL context without the use of VR technology for viewing and solving the identical scenario. After the intervention, all the students wrote a problem‐solving analysis, took a vocabulary knowledge test, completed a learning motivation questionnaire, and participated in individual interviews. The results showed that the students in the experimental group significantly outperformed those in the control group in terms of vocabulary acquisition, and were more motivated to learn English related to their future careers, whereas there was no significant difference in the problem‐solving performance of the two groups. Implications of these findings highlight the value of engaging EFL learners in immersive environments for contextualized learning through the integrated use of VR and PBL. Lay Description: What is already known about this topic?: Virtual reality (VR) technology has been shown to enhance students' knowledge and skills in STEM fields. Problem‐based learning (PBL) has been widely used in medical education but not so much in foreign language education. English as a foreign language (EFL) students usually have very limited access to the target language beyond the classroom, thus lack a motivating reason for them to learn English after graduation. What this paper adds?: The VR‐assisted PBL approach proposed in this study was found to significantly enhance the EFL students' specialized vocabulary knowledge. The VR‐assisted PBL approach was found to motivate and sustain the EFL students' interest in career English. Exposing the EFL students to PBL contexts was capable of developing their problem‐solving performance, regardless of VR integration. Implications for practice and/or policy: The proposed approach has the potential to facilitate student learning in EFL education, particularly English for occupational purposes. EFL educators may apply the VR‐assisted PBL approach to narrow the gap between language classrooms and workplace contexts by immersing students in authentic contexts that were relevant to their occupational knowledge and workplace English.